Coupling tyrosol, quercetin or ferulic acid and electron beam irradiation to cross-link chitosan–gelatin films: A structure–function approach. (June 2015) - Benbettaïeb, Nasreddine; Karbowiak, Thomas; Brachais, Claire-Hélène; Debeaufort, Frédéric
Graphical abstract: Influence of 5% antioxidant content and 60 kGy irradiation dose on the oxygen permeability of chitosan–fish gelatin film at 53% RH and 25 °C. Highlights: Chitosan–gelatin films containing antioxidants were irradiated by electron beam. The generation of free radicals induces crosslinking in the biopolymer network. Mechanical and barrier properties affected by both antioxidants and irradiation. Peculiar behaviour of properties of films containing ferulic acid. Abstract: Marine industry by-products, chitosan and fish gelatin, entrapping natural antioxidants (ferulic acid, quercetin and tyrosol) were used to prepare edible active films by casting. The films were composed of chitosan and fish gelatin (1:1 w:w) and incorporating antioxidants (∼50 mg/g). After solvent evaporation (drying), the films were irradiated at 60 kGy by electron beam. This treatment aims at investigating the coupled effect of irradiation with the presence of active compound on the structure and functional properties of the films. Electron Spin Resonance (ESR) unravelled free radical formation during irradiation in films containing ferulic acid or tyrosol which favoured cross-linking between biopolymers. Then, some films became stiffer, the tensile strength increased after the incorporation of antioxidants and/or after irradiation. As expected, as the tensile strength increased, the % of elongation of irradiated and antioxidant-containing films was reduced, except for the irradiated control films. The enhancement of water barrier properties, measured using a 0–30% RH gradient, was observed after ferulic acid and tyrosol additions but remained unchanged after irradiation treatment. A synergic effect of irradiation and active compounds addition was noteworthy on the oxygen barrier properties. Irradiation and antioxidants also induced a slight enhancement of the thermal stability. The surface tension and its dispersive component significantly increased after the incorporation of antioxidants. On the contrary, a significant increase of the polar component is observed for the film containing ferulic acid. Irradiation accentuated the wettability and the hydrophilicity of the film containing quercetin and tyrosol. These results clearly showed that interactions between the polymer chains and/or between the polymer chains and the antioxidants after irradiation were favoured by both antioxidant addition and electron beam treatment. This is confirmed on a molecular scale from the peak shifts observed in amide and carbonyl groups as observed from FTIR.